2005
DOI: 10.1111/j.1523-1739.2005.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional IUCN Red Listing: the Process as Applied to Birds in the United Kingdom

Abstract: The World Conservation Union (IUCN) has developed guidelines that enable the assessment of extinction risk at a regional scale. We used these guidelines to assess the extinction risk of birds in the United Kingdom for comparison with an existing assessment of conservation status. Sixty-four species were categorized as regionally threatened, of which 12 were critically endangered. The categorizations of the 223 species assessed agreed broadly with those from the existing U.K. system, which considers more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 11 publications
1
48
1
Order By: Relevance
“…It is suggested that experts involved in the assessments were too strict in the application of the new IUCN C&C and did not sufficiently correct their assessments based on expert opinion, which may in a number of cases have resulted in a higher threat category on the IUCNcriteria based Red List. This is contrary to Eaton et al (2005), who concluded in a comparative study of a national Red List for birds in the UK using the UK system and the new IUCN C&C, that the IUCN Red List depended heavily upon the subjective decisions made during the assessment process. Eaton et al (2005) also concluded that in their study the total number of 223 red listed birds on the IUCN Red List broadly agreed with the UK Red List, but that there was also (and this is also true for the Dutch experience with birds and butterflies) a tendency for the IUCN process to give higher risk status to edge of the range species and low status to those that have declined but remain common.…”
Section: International Harmonization Of Red Listscontrasting
confidence: 46%
See 1 more Smart Citation
“…It is suggested that experts involved in the assessments were too strict in the application of the new IUCN C&C and did not sufficiently correct their assessments based on expert opinion, which may in a number of cases have resulted in a higher threat category on the IUCNcriteria based Red List. This is contrary to Eaton et al (2005), who concluded in a comparative study of a national Red List for birds in the UK using the UK system and the new IUCN C&C, that the IUCN Red List depended heavily upon the subjective decisions made during the assessment process. Eaton et al (2005) also concluded that in their study the total number of 223 red listed birds on the IUCN Red List broadly agreed with the UK Red List, but that there was also (and this is also true for the Dutch experience with birds and butterflies) a tendency for the IUCN process to give higher risk status to edge of the range species and low status to those that have declined but remain common.…”
Section: International Harmonization Of Red Listscontrasting
confidence: 46%
“…The different outcomes of the IUCN Red Lists compared with the Red Lists using the national system found in the Dutch pilot and in the UK study by Eaton et al (2005) may have important consequences for overall national nature conservation priorities. Although more and more European countries have now started using the new IUCN C&C (for example Finland, Sweden, Switzerland, the UK, the Netherlands), a substantial number of countries, among them the Netherlands, still make use of their own criteria or of modified IUCN criteria for national policy purposes.…”
Section: International Harmonization Of Red Listsmentioning
confidence: 99%
“…It could be useful for the relatively small well-studied countries or for some well-known taxa, but the assessment of big territories or scarcely studied groups always result in difficulties with its use. So, the assessment of biodiversity of Finland (Juslén et al, 2013), birds of Britain (Eaton et al, 2005) or Switzerland (Keller et al, 2005), butterflies of Flanders (Maes et al, 2012), re-assessment of 163 rare species of Asian countries (Millner-Gulland et al, 2006) did not provoke serious disagreements with IUCN schemes. On the contrary, comparison of the IUCN list with US Endangered species act (Harris et al, 2013) or with the red lists of Brazil, Colombia, China and the Philippines (Brito et al, 2010) revealed numerous mismatches.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the resulting threat status for a particular species is also taken as a measurement for conservation priorities, even though red lists were not designed for that purpose. However, red lists may at best be a suboptimal tool for setting conservation priorities in a country or region as the threat status does not always reflect actual conservation needs (Gärdenfors 2000(Gärdenfors , 2001Mehlman et al 2004;Eaton et al 2005). That is especially true from an international point of view, from which it is clearly more desirable to focus national conservation efforts on the near-endemics centred in the respective country (Schnittler and Günther 1999).…”
Section: Introductionmentioning
confidence: 96%